2022
DOI: 10.3171/2022.4.focus2291
|View full text |Cite
|
Sign up to set email alerts
|

Emerging pathogenic mechanisms in human brain arteriovenous malformations: a contemporary review in the multiomics era

Abstract: A variety of pathogenic mechanisms have been described in the formation, maturation, and rupture of brain arteriovenous malformations (bAVMs). While the understanding of bAVMs has largely been formulated based on animal models of rare hereditary diseases in which AVMs form, a new era of “omics” has permitted large-scale examinations of contributory genetic variations in human sporadic bAVMs. New findings regarding the pathogenesis of bAVMs implicate changes to endothelial and mural cells that result in increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Brain AVMs are masses of abnormal vessels characterized by direct connections between arteries and veins without intervening capillaries that aggregate into a nidus and associated perinidal networks. 76 These lesions can be composed of single or multiple compartments and include numerous feeding arteries and draining veins. 77 The majority of bAVMs are congenital and are thought to arise in the 4th–8th week of embryonic development – the period during which the potential boundary of the vascular malformation is defined – with the ultimate angioarchitecture of the bAVM determined by cellular and molecular interactions throughout develpoment.…”
Section: Macrophages In Intrinsic Pathologies Of Vascular Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain AVMs are masses of abnormal vessels characterized by direct connections between arteries and veins without intervening capillaries that aggregate into a nidus and associated perinidal networks. 76 These lesions can be composed of single or multiple compartments and include numerous feeding arteries and draining veins. 77 The majority of bAVMs are congenital and are thought to arise in the 4th–8th week of embryonic development – the period during which the potential boundary of the vascular malformation is defined – with the ultimate angioarchitecture of the bAVM determined by cellular and molecular interactions throughout develpoment.…”
Section: Macrophages In Intrinsic Pathologies Of Vascular Developmentmentioning
confidence: 99%
“…82 The growth and progression of bAVMs involves chronic interplay between endothelial cells, smooth muscle cells, pericytes, and peripheral leukocytes. 76 Interactions between leukocytes and the vessel wall during bAVM growth and hemorrhage have recently provided new insights into bAVM biology. 83 Clinically, approximately 50% of symptomatic bAVMs present hemorrhagically, 20–45% with seizures, and the remaining with headaches, neurological deficits, or incidentally.…”
Section: Macrophages In Intrinsic Pathologies Of Vascular Developmentmentioning
confidence: 99%
“…The majority of familial AVM cases (about 5% of all AVM cases) are associated with hereditary hemorrhagic telangiectasia (HHT) and capillary malformation-arteriovenous malformation syndrome, both of which are autosomal dominant inherited genetic conditions. [27,28]) Preclinical investigations have attempted to isolate the genes that lead to cerebral AVM in these diseases. It has been shown that congenital mutations in the TGF-β and RAS vascular signaling pathways result in an increased risk of cerebral AVM formation [29,30].…”
Section: Etiologymentioning
confidence: 99%
“…It has been shown that congenital mutations in the TGF-β and RAS vascular signaling pathways result in an increased risk of cerebral AVM formation [29,30]. This research has primarily been focused on the genes that code for Endoglin (ENG) and Activin A receptor type II-like 1 (ALK1) [27,28,31]. About 95% of AVM cases are not related to familial conditions [32].…”
Section: Etiologymentioning
confidence: 99%
“…In recent years, multi-omics technologies including genomics, transcriptomics, metabolomics, and proteomics have been widely used to explore the mechanisms of various diseases ( Ohashi et al, 2015 ), including but not limited to Alzheimer’s disease, human brain arteriovenous malformation, and other brain diseases ( Wang et al, 2021 ; Winkler et al, 2022 ). In a previous study, Zhong et al (2016) used transcriptomic techniques to observe changes of mRNA and lncRNA expression in the cortex of TBI model mice.…”
Section: Introductionmentioning
confidence: 99%